THE SUPPORT OF SCIENCE IN JAPAN: ORGANIZATIONAL FORMS AND FINANCIAL MECHANISMS - Pronichkin, S. V. (Vestnik MGIMO-Universiteta, 2016)
Recent organizational and structural changes have significantly changed the relative importance of research funding mechanisms in Russia. There is a need for understanding the possible effects of changes to Russian science. In this context, particular important to research a foreign experience of research funding. For example in Japan have developed a new approach to research funding. It is important to consider the essence of the new approach to research funding, in the aspect of national characteristics of research policy in Japan. It is also necessary to take into account the specific activities of the research funding institutions. The article highlights the advantages and disadvantages of the traditional mechanisms of research funding in Japan. The author draws parallels between the approaches to research funding by the Japan Society for the Promotion of Science and the Japan Science and Technology Agency. The recent changes in research policy, which led to development of the new funding scheme are described. The new research funding scheme is analyzed. The necessary conditions for effectively functioning of the new research funding scheme are identified. These conditions include adequacy of funding, mobility of research personnel, advanced research infrastructure, high absorption capability of the private sector.